Izdelava velikih glivnih biokompozitov z nizko gostoto - Bizjak, Nej (Les (Ljubljana), 2024)
As the need for a circular economy grows, so does the need for new sustainable materials. Biocomposites made from fungi are a sustainable alternative to synthetic foams. The key to commercializing this technology is knowing how to produce large quantities of such materials with the appropriate properties. As part of our experimental work, we have produced a larger mycelium biocomposite with a low density, a volume of 47 litres and a length of two metres. The final fungal biocomposite was produced by growing the mycelium in three stages; first in culture bags, then in two larger moulds, which were combined in a third stage. We used a culture of Ganoderma resinaceum and a specially formulated substrate to achieve a low density. The final biocomposite with a density of 80 kg/m3 met the target dimensions, remained infection-free and withstood lighter loads. The main disadvantage of the material was the small surface indentations caused by air inclusions in the substrate when the mycelium-laden substrate was transferred to the moulds.
Keywords: biocomposites; biokompoziti; fungi; glive; materiali iz micelija; micelij; mycelium; mycelium materials